Schubert polynomial expansions revisited - Philippe Nadeau; Hunter Spink; Vasu Tewari (Forum of Mathematics, Sigma)
We give an elementary approach utilizing only the divided difference formalism for obtaining expansions of Schubert polynomials that are manifestly nonnegative, by studying solutions to the equation